(untitled) (Research, Society and Development, 2021)
Background: Even though complications involving dental needles are currently rare, accidents are likely to occur, mainly in lower alveolar nerve block due to numerous factors inherent to the operator and / or the material itself. The management of these patients aims to remove the needle immediately, if the tip is visible, or to apply methods to locate the needle in the pterygomandibular space. These methods range from simple radiographs to the use of modern scanners, always aiming at patient comfort and quick resolution of the condition. Objective and case report: The objective of this article is to report a clinical case of the use of the image intensifier to remove a fractured needle after anesthesia of the lower alveolar nerve, during an extraction procedure. Male patient, 28 years old, referred to the emergency department, without pain complaints. Surgical removal with the aid of the image intensifier of the fractured gingival needle lodged in the left mandibular ascending branch, was performed under general anesthesia, by means of an access in the region of the jugal mucosa. Conclusion: To prevent fractures of gingival needles in dental procedures, it is necessary to perform the correct anesthetic technique, avoiding needle bends. In the case of needle fractures, we can conclude that additional methods, such as the use of the image intensifier, help the removal causing less tissue damage, consequently less patient morbidity.